Mesenchymal stem cells and their extracellular vesicle therapy for neurological disorders: traumatic brain injury and beyond - Yarahmadi, Aref; Dorri Giv, Masoumeh; Hosseininejad, Reza; Rezaie, Azin; Mohammadi, Narges; Afkhami, Hamed; Farokhi, Arastoo (Frontiers in Neurology, 2025)
Traumatic brain injury (TBI) is a complex condition involving mechanisms that lead to brain dysfunction and nerve damage, resulting in significant morbidity and mortality globally. Affecting 50 million people annually, TBI's impact includes a high death rate, exceeding that of heart disease and cancer. Complications arising from TBI encompass concussion, cerebral hemorrhage, tumors, encephalitis, delayed apoptosis, and necrosis. Current treatment methods, such as pharmacotherapy with dihydropyridines, high-pressure oxygen therapy, behavioral therapy, and non-invasive brain stimulation, have shown limited efficacy. A comprehensive understanding of vascular components is essential for developing new treatments to improve blood vessel-related brain damage. Recently, mesenchymal stem cells (MSCs) have shown promising results in repairing and mitigating brain damage. Studies indicate that MSCs can promote neurogenesis and angiogenesis through various mechanisms, including releasing bioactive molecules and extracellular vesicles (EVs), which help reduce neuroinflammation. In research, the distinctive characteristics of MSCs have positioned them as highly desirable cell sources. Extensive investigations have been conducted on the regulatory properties of MSCs and their manipulation, tagging, and transportation techniques for brain-related applications. This review explores the progress and prospects of MSC therapy in TBI, focusing on mechanisms of action, therapeutic benefits, and the challenges and potential limitations of using MSCs in treating neurological disorders.